O Flourishing Business Canvas como ferramenta para a modelagem de negócios sustentáveis em startups - Pellin, Alecxandro (2022)
This research, one of the pioneers in Brazil, aimed to investigate the use of the Flourishing Business Canvas as a tool for the elaboration of sustainable business models by startups. Startups are companies with potentially scalable business models and inserted in an environment of extreme uncertainty, thus, as they develop their products or services, they cannot be indifferent to the assumptions of sustainability. In this context, the need for tools that can help these companies transform their current business model into a new model concept focused on sustainability is evident, and the Flourishing Business Canvas has this premise. Thus, to achieve the proposed objective, the study is carried out through a qualitative approach with a technical procedure of action research, with the realization of workshops with four startups using the Flourishing Business Canvas. In the workshops, the applicability and usefulness of the tool is evaluated based on the perceptions of the participants and systematic direct observation by the researcher, while the startups build or adapt their current conventional business model to a sustainable model, integrating the economic, environmental, and social contexts. The results of the research showed that the Flourishing Business Canvas is a potential tool for sustainable business modeling by startups. It can be employed to understand the sustainability practices and actions of these companies as a whole, showing their social, environmental, and economic sustainability in a schematic and strategic way, and consequently be used as a tool for modeling their business with the claim of being effectively sustainable. This study contributes theoretically to the literature with its detailed examination of the tool and the proof of its effectiveness and usefulness when applied to startups. It presents important considerations about the tool's usability and possible improvements, thus contributing to a future agenda of studies. It also contributes to the practice by providing with the study a holistic view of sustainability for the participants, encouraging the ideation and visualization of their business model allied to the concern with social and environmental improvement of these companies.